Analysis Of Financial Performance At The Savings And Loan Cooperative Simpati Manna Sub-District South Bengkulu District - Anisa, Nur; Susanti, Neri; Astuty , Kamelia (Universitas Dehasen Bengkulu, 2024)
Simpati Savings and Loan Cooperative is one of the cooperatives in Manna, South Bengkulu. Cooperatives like other companies, have the aim of getting a large profit or profit. The purpose of this study was to analyze the financial performance of Simpati Savings and Loan Cooperative in Manna District, South Bengkulu Regency. The type of research used in this research is quantitative research with a descriptive approach. Data collection techniques using documentation and library techniques. The data analysis technique uses quantitative by calculating financial ratios including current ratio, debt to equity ratio, total asset turnover, return on assets from 2020 to 2022 at Simpati Cooperative, Manna District, South Bengkulu Regency. The results showed that the financial performance of the Simpati Manna South Bengkulu cooperative based on the liquidity ratio for the 2021-2022 period was in the healthy category with a current ratio indicator value in 2021 of 191.88% and in 2022 of 178.67%, a quick ratio indicator in 2021 of 146.29% and in 2022 of 146.60% cash ratio indicator in 2021 of 231.07% and in 2022 of 223.39%. The financial performance of the Simpati Manna South Bengkulu cooperative based on the profitability ratio for the 2021-2022 period is in the very healthy category with an economic profitability value in 2021 of 8.19% and in 2022 of 10.845 the value of own capital profitability in 2021 of 28.96% and in 2022 of 36.98%. The financial performance of the Simpati Manna South Bengkulu cooperative based on the solvency ratio for the 2021-2022 period is in the unhealthy category, the debt to asset ratio (DAR) indicator in 2021 is 48.25% and in 2022 it is 51.79%; the debt to equity ratio indicator in 2021 is 226.15% and in 2022 it is 272.55%. The financial performance of the Simpati Manna South Bengkulu cooperative based on the profitability ratio for the 2021-2022 period is in the healthy category with a profit magin indicator value on sale in 2021 of 9.14% and in 2022 of 11.67%; return on investment (ROI) value in 2021 of 2.69% and in 2022 of 3.31%; return on equity indicator in 2021 of 12.92% and in 2022 of 18.35%.